2021
DOI: 10.3389/fmed.2021.651559
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Efficiency of Non-drug Therapy Among Community-Dwelling Adults With Hypertension in China: A Protocol for Network Meta-Analysis and Cost-Effectiveness Analysis

Abstract: Introduction: The Chinese government has established a nationwide community-based chronic disease management program since 2009 with hypertension a vital part of it. Though drugs have been proven effective with hypertensive patients, they bring economic burden as well, especially for those who with elevated blood pressure and are potentially eligible for national programs. When the effectiveness of pharmacotherapy-only interventions remains uncertain on these patients, non-pharmacological interventions have de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…This research was reported following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) checklist (26). This research was registered with PROSPERO (registration number: CRD42020151518) and the protocol has been published (27).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This research was reported following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) checklist (26). This research was registered with PROSPERO (registration number: CRD42020151518) and the protocol has been published (27).…”
Section: Methodsmentioning
confidence: 99%
“…However, blinding and allocation concealment would be difficult to achieve in NPIs. Therefore, we would make particular note of articles that did not involve blinding and allocation concealment but had valuable data (27).…”
Section: Risk Of Bias and Evidence Quality Assessmentmentioning
confidence: 99%
“…However, it is the high calorie food consumption and sedentary lifestyle habits that conflict with LSM and affect adherence to implementation in people with PHT. A number of studies are now emerging that provide evidence for pharmacological treatment, but long-term drug use places a financial burden on the healthcare system and families ( 12 ). Previous studies have included BP across both PHT and HT populations, and fewer studies have discussed pharmacological and non-pharmacological interventions together.…”
Section: Introductionmentioning
confidence: 99%
“…We modeled the posttreatment prognosis of skin lesions using transition diagrams among skin lesion scales. A transition diagram is a widely used tool for assessing disease development in chronic diseases [23][24][25] and models the probabilities of transitioning among health stages over time. 26 It is useful for understanding the course of diseases and the chances of getting better.…”
Section: Introductionmentioning
confidence: 99%